Syphilis Trends among Men Who Have Sex with Men in the United States and Western Europe: A Systematic Review of Trend Studies Published between 2004 and 2015. - Winston E Abara; Kristen L Hess; Robyn Neblett Fanfair; Kyle T Bernstein; Gabriela Paz-Bailey (PLoS ONE)
Globally, men who have sex with men (MSM) are disproportionately burdened with syphilis. This review describes the published literature on trends in syphilis infections among MSM in the US and Western Europe from 1998, the period with the fewest syphilis infections in both geographical areas, onwards. We also describe disparities in syphilis trends among various sub-populations of MSM. We searched electronic databases (Medline, Embase, Global Health, PsychInfo, CAB Abstracts, CINAHL, Sociological Abstracts, Web of Science, Cochrane Library, and LILACS) for peer-reviewed journal articles that were published between January 2004 and June 2015 and reported on syphilis cases among MSM at multiple time points from 1998 onwards. Ten articles (12 syphilis trend studies/reports) from the US and eight articles (12 syphilis trend studies/reports) from Western Europe were identified and included in this review. Taken together, our findings indicate an increase in the numbers and rates (per 100,000) of syphilis infections among MSM in the US and Western Europe since 1998. Disparities in the syphilis trends among MSM were also noted, with greater increases observed among HIV-positive MSM than HIV-negative MSM in both the US and Western Europe. In the US, racial minority MSM and MSM between 20 and 29 years accounted for the greatest increases in syphilis infections over time whereas White MSM accounted for most syphilis infections over time in Western Europe. Multiple strategies, including strengthening and targeting current syphilis screening and testing programs, and the prompt treatment of syphilis cases are warranted to address the increase in syphilis infections among all MSM in the US and Western Europe, but particularly among HIV-infected MSM, racial minority MSM, and young MSM in the US.